NEGOSIASI BUDAYA DALAM OLAHRAGA (Studi Kasus Atlet Berhijab Figure skating Pertama Uni Emirat Arab) - Faiza Kintan Maharani; Ade Solihat (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2023)
The phenomenon of hijab is creating more and more space for consideration. The use of hijab among female athletes in various sports is increasing. This research discusses the clothing performance of Zahra Lari, a figure skating athlete from Abu Dhabi, United Arab Emirates. Figure skating is a sport performed by dancing on ice with tight clothing attached to the athlete's body. This type of tight-fitting clothing is aerodynamic and lightweight to make it easier for athletes to move without feeling overloaded. Zahra Lari was the first female athlete to wear the hijab at the 2012 European Cup Winter Championships in Italy. Zahra Lari received a deduction in the competition due to her unusual use of the hijab. The deduction made Zahra Lari appeal to the International Skating Union (ISU), because she felt unfairly treated. The appeal was eventually accepted by the ISU and since then many figure skating athletes have worn the hijab in various competitions. Zahra Lari's efforts to negotiate the figure skating clothing model with the addition of hijab is the focus of this research. This research aims to explain how Zahra Lari negotiates culture in order to be accepted to compete in international figure skating competitions without leaving her attitude and worldview in dressing. This research uses a qualitative method. Data collection techniques were carried out by studying English-language media and remote interviews. Interviews were conducted with Zahra Lari as the main informant. Interviews were also conducted with a figure skating coach in Kuwait and a Kuwaiti national figure skating athlete. The results showed that Zahra Lari's cultural negotiation had an impact on cultural harmonisation in figure skating.